HIMMELFARB: O PAPEL DAS EMOÇÕES NO PROCESSO DE PERCEPÇÃO (CULTURAL) - Mathias, Dionei (Línguas & Letras, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>